4(5-2n)=8(-6-5n)

Simple and best practice solution for 4(5-2n)=8(-6-5n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5-2n)=8(-6-5n) equation:


Simplifying
4(5 + -2n) = 8(-6 + -5n)
(5 * 4 + -2n * 4) = 8(-6 + -5n)
(20 + -8n) = 8(-6 + -5n)
20 + -8n = (-6 * 8 + -5n * 8)
20 + -8n = (-48 + -40n)

Solving
20 + -8n = -48 + -40n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '40n' to each side of the equation.
20 + -8n + 40n = -48 + -40n + 40n

Combine like terms: -8n + 40n = 32n
20 + 32n = -48 + -40n + 40n

Combine like terms: -40n + 40n = 0
20 + 32n = -48 + 0
20 + 32n = -48

Add '-20' to each side of the equation.
20 + -20 + 32n = -48 + -20

Combine like terms: 20 + -20 = 0
0 + 32n = -48 + -20
32n = -48 + -20

Combine like terms: -48 + -20 = -68
32n = -68

Divide each side by '32'.
n = -2.125

Simplifying
n = -2.125

See similar equations:

| 450=3x^2-30x-150 | | .02x^2+3x-2000=0 | | 3N-5=-9(6+5N) | | 7400=x^2-70x+4400 | | 0.5y=10-0.3y | | (I+3i)+(1+2i)= | | [(2x+25)(2x+13)]-(25*13)=160 | | [(2x+25)(2x+13)]-(25*13)=480 | | .16*36+61=x | | 2.3x^2-3.5x-1.2=0 | | x^2+10x=-11 | | x^2+16x=-42 | | -2(n-8)=-(2n-1)+5n | | x^2-12+36= | | 1+3(5-3x)=4-6(-2+8x) | | 2.8y+8.6=9.12-1.2 | | (6+.50*4)3=3 | | -17-v=3v+3(3+3v) | | 7(8x-1)+6=-169 | | 2m^2+5m-21=0 | | -199=5(1-5m)-4 | | 81x^2-169=0 | | g^2+7g+12=0 | | 3x+6+5+x-10=180 | | 5(3-x)+2(x+1)=x+5 | | 2g-4+10g+12= | | 2c+9=9c+5 | | 28x^2-63=0 | | -4=5z | | 3g+5=79+4 | | 5z+1=10z+5 | | 2x-1/3-x-5/6=x-3/4 |

Equations solver categories